There are two answers and they are x = -4 and x = -14
========================================================
Step-by-step explanation:
Apply the square root to both sides
(x+9)^2 = 25 leads to x+9 = 5 or x+9 = -5
This is because (-5)^2 = 25 and (5)^2 = 25. This is the plus/minus you often see with quadratics.
Solve x+9 = 5 to get x = -4. We subtract 9 from both sides to get this.
Solve x+9 = -5 to get x = -14
That's why the two answers are x = -4 and x = -14.
------
To check our answers, we plug those x values into the original equation and simplify. We should get the same thing on both sides
(x+9)^2 = 25
(-4+9)^2 = 25 ... replace x with -4
(5)^2 = 25
25 = 25 ... So x = -4 has been confirmed
and,
(x+9)^2 = 25
(-14+9)^2 = 25 ... replace x with -14
(-5)^2 = 25
25 = 25 ... and x = -14 has been confirmed